Anticancer, antioxidant activities, and DNA affinity of novel monocationic bithiophenes and analogues - Ismail MA; Arafa RK; Yousssef MM; El-Sayed WM (Dove Medical Press, 2014)
Mohamed A Ismail,1,2 Reem K Arafa,3 Magdy M Youssef,1,2 Wael M El-Sayed1,4 1Departments of Chemistry and Biological Sciences, College of Science, King Faisal University, Hofuf, Saudi Arabia; 2Department of Chemistry, Faculty of Science, Mansoura University, Mansoura, Egypt; 3Department of Pharmaceutical Chemistry, Faculty of Pharmacy, Cairo University, Cairo, Egypt; 4Department of Zoology, Faculty of Science, University of Ain Shams, Abbassia, Cairo, Egypt Abstract: A series of 15 monocationic bithiophenes and isosteres were prepared and subjected to in vitro antiproliferative screening using the full National Cancer Institute (NCI)-60 cell line panel, representing nine types of cancer. Among the nine types of cancer involved in a five-dose screen, non-small cell lung and breast cancer cell lines were the most responsive to the antiproliferative effect of the tested compounds, especially cell lines A549/ATCC, NCI-H322M, and NCI-H460, whereas compounds 1a, 1c, 1d, and 7 exhibited potent activity, with GI50 values (drug concentration that causes 50% inhibition of cell growth) from less than 10 nM to 102 nM. In addition, compounds 1c and 1d gave GI50 values of 73 nM and 79 nM, respectively, against the MDA-MB-468 breast cancer cell line. Structure–activity relationship findings indicated that the mononitriles were far less active than their corresponding monoamidines and, within the amidines series, the bioisosteric replacement of a thiophene ring by a furan led to a reduction in antiproliferative activity. Also, molecular manipulations, involving substitution on the phenyl ring, or its replacement by a pyridyl, or alteration of the position of the amidine group, led to significant alteration in antiproliferative activity. On the other hand, DNA studies demonstrated that these monoamidine bichalcophenes have promising ability to cleave the genomic DNA. These monoamidines show a wide range of DNA affinities, as judged from their DNA cleavage effect, which are remarkably sensitive to all kinds of structural modifications. Finally, the novel bichalcophenes were tested for their antioxidant property by the ABTS (2,2'-azino- bis(3-ethylbenzthiazoline-6-sulfonic acid) diammonium salt) assay, as well as lipid and nitric oxide scavenging techniques, and were found to exhibit good-to-potent antioxidant abilities. Keywords: bithiophenes, anticancer, DNA cleavage, antioxidant, Suzuki coupling, Stille coupling